Social participation patterns and associations with subsequent cognitive function in older adults with cognitive impairment: a latent class analysis - Li, Xin; Feng, Haishan; Chen, Qingling (Frontiers in Medicine, 2025)
BackgroundSocial participation (SP) has been associated with cognitive benefits among older adults; however, little is known about SP patterns and their relationships with cognitive function in cognitively impaired populations. This study aimed to identify SP patterns among cognitively impaired older individuals and evaluate their associations with subsequent cognitive function, specifically mental intactness and episodic memory.MethodsData were drawn from the China Health and Retirement Longitudinal Study (CHARLS), including 5,673 individuals aged 60 years and older with cognitive impairment from 2015 to 2018. Latent class analysis (LCA) was used to identify SP patterns, and hierarchical linear regression analyses were conducted to examine associations between these patterns and cognitive function.ResultsFour distinct SP patterns were identified: “Offline Social Participation Group” (Class 1), “Intellectual Social Participation Only Group” (Class 2), “Club and Volunteer Activities Group” (Class 3), and “Minimal Social Participation Group” (Class 4). The Class 4 comprised the majority (73%) and exhibited the poorest cognitive outcomes. Compared to the Class 4, Class 2 showed significant improvements in mental intactness (p < 0.001) and episodic memory (p = 0.022), while Class 3 demonstrated significant improvements in mental intactness (p = 0.032) but not episodic memory. Class 1 showed significant improvements in episodic memory (p = 0.023).ConclusionThis study highlights the cognitive benefits of social participation, particularly intellectual activities, for older adults with cognitive impairment. Targeted interventions promoting SP, especially intellectual activities, are essential to mitigate cognitive decline and improve cognitive resilience in vulnerable populations.